Electrospun Nano- and Microfiber Mesh-Based Transducer for Electrochemical Biosensing Applications - Alexander M. Lloyd; Willem J. Perold; Pieter R. Fourie (Engineering Proceedings, 2023)
Biosensors hold great promise as diagnostic devices that gain the information needed to discern between different types and severities of infection. Accurate diagnostic information allows for appropriate antimicrobial usage, thereby benefiting patient welfare and curbing the development of antimicrobial resistance. With these aims in mind, a nano- and microfiber mesh-based transducer platform for use in aqueous media was developed. When used in an electrochemical cell, this transducer is able to distinguish between different concentrations of phosphate-buffered saline in deionized water using electrochemical impedance spectroscopy. This transducer, when coupled with a biorecognition element, could serve as a new biosensor platform, to be employed as a diagnostic device that could be applied to various biological targets.